Trichoribates and Jugatala (Acari: Oribatida: Ceratozetidae) from the Central and Southern Alps, with notes on their distribution - Bayartogtokh, Badamdorj; Schatz, Heinrich (Zootaxa, 2008)
The present paper deals with five species of oribatid mites of the genus Trichoribates Berlese, 1910 and two species of the genus Jugatala Ewing, 1913 from high mountains of the Central and Southern Alps. A new species, Trichoribates scilierensis sp. nov., collected from South Tyrol (Italy) is described in detail on the basis of adults. In addition, supplementary descriptions and illustrations of six known species, Trichoribates monticola (Trägårdh, 1902), T. novus (Sellnick, 1928), T. punctatus Shaldybina, 1971, T. trimaculatus (C. L. Koch, 1835), Jugatala angulata (C. L. Koch, 1839) and J. cribelliger (Berlese, 1904) are presented. Trichoribates punctatus is recorded for the first time in Central Europe. The status of old generic names as well as the validity of some species are discussed. The synonymy of T. oxypterus (Berlese, 1910) is rejected and its validity retained. The possible synonymy of Jugatala rotunda Willmann, 1953 with J. angulata is discussed. The distribution of all studied species is discussed.